Respuesta :
Answer:
-1
Step-by-step explanation:
3+-4
Since the signs are opposite, we subtract the two numbers and take the sign of the larger
4-3 =1
The sign of the larger number (-4) is negative
-1
3+-4 = -1
For this case, what we must do is solve the following algebraic expression:
[tex]3 + (-4)[/tex]
According to the law of signs we have to:
[tex]+ * + = +\\+ * - = -\\- * - = +[/tex]
Thus, applying the aforementioned law we have to: [tex]3 + (-4) = 3-4[/tex]
Rewriting we have:
[tex]3 + (-4) = -1\\[/tex]
Answer:
[tex]3 + (-4) = -1\\[/tex]